2021
DOI: 10.3389/fphys.2021.648950
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Plot-Based Approach for Cardiac Arrhythmia Classification Using Inception-ResNet-v2

Abstract: The present study addresses the cardiac arrhythmia (CA) classification problem using the deep learning (DL)-based method for electrocardiography (ECG) data analysis. Recently, various DL techniques have been utilized to classify arrhythmias, with one typical approach to developing a one-dimensional (1D) convolutional neural network (CNN) model to handle the ECG signals in the time domain. Although the CA classification in the time domain is very prevalent, current methods’ performances are still not robust or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
0
20
0
2
Order By: Relevance
“…Table 16 compares the results of this study with those reported in other publications with respect to their respective arrhythmia categories, segment lengths, and average accuracies using various databases (mainly the MITDB). The Inception-ResNet-v2 network with RP images was used in Zhang et al [64] as a classification method for cardiac arrhythmias. The CPSC database detected nine types of arrhythmias in their proposed work.…”
Section: Discussionmentioning
confidence: 99%
“…Table 16 compares the results of this study with those reported in other publications with respect to their respective arrhythmia categories, segment lengths, and average accuracies using various databases (mainly the MITDB). The Inception-ResNet-v2 network with RP images was used in Zhang et al [64] as a classification method for cardiac arrhythmias. The CPSC database detected nine types of arrhythmias in their proposed work.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ECG-based experiments, the 12-lead ECG signals were transformed into 2DRP images and stacked together to form 3D images, as illustrated in Figure 4. The method of converting 1D ECG signals into the corresponding 2DRP images is reported in our previous work (Zhang et al, 2021). Then we applied with (min-max and z-score normalization) and without normalization to pre-process the 2D RPs, respectively, which are defined as follows.…”
Section: Experimental Designmentioning
confidence: 99%
“…After normalization, these 12 leads images were placed with the lead-index order of limb leads (lead I, II, III, aVR, aVL, aVF) followed by the chest leads (V1, V2, V3, V4, V5, V6) to form as a 3DRP image. In our previous work (Zhang et al, 2021), we used those 2D RP plots (see Figure 4) to train the network and detect 2D RP features for classification. The relationship between the leads is implicitly investigated by the network, which is essential to explore but less obvious to learn from the 2D textures.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations